SACROCOCCYGEAL TERATOMA, CASE REPORT - Bashir fazari, Atif; A.Musharaf, Khalifa; Ahmed, Badreldeen (Gezira Journal of Health Sciences; Vol 5 No 1 (2009), 2009)
Sacrococcygeal teratoma (SCT) is the most common tumor presenting at birth. Commonly seen in female fetuses; this case presented, more or less with the whole feature of typical sacrococcygeal teratoma.